Pengembangan Media Misteri Pecahan (RIHAN) Berbasis Realistic Mathematics Education untuk Meningkatkan Pemahaman Konsep Matematika Siswa - Harwiyati, Windi; Fitriani, Andhin Dyas; Mufliva, Rosiana (Circle: Jurnal Pendidikan Matematika, 2025)
This study aims to develop teaching materials to improve students’ conceptual understanding of fractions. The research employed a Design and Development method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The data obtained were both qualitative and quantitative. Qualitative data were collected from expert validators’ suggestions, while quantitative data were derived from validators’ assessments and student test results. The research subjects were 17 fourth-grade elementary school students in Bandung. The findings revealed that the teaching material RIHAN achieved a feasibility score of 90.3% from material, language, and design experts, and 92.5% from teacher practitioners, categorized as highly feasible. Furthermore, the effectiveness test showed an N-gain score of 0.533 (moderate category), indicating an improvement in students’ conceptual understanding. Therefore, the RIHAN teaching material is considered feasible and effective for enhancing elementary school students’ conceptual understanding of fractions.